ZrO2-CNT composite production through reducing atmosphere - Neto, Vicente Gerlin; Pereira, Cristian Guilherme Barbosa [UNESP]; Faglioni, Felipe Dias [UNESP]; Fortulan, Carlos Alberto; Foschini, Cesar Renato [UNESP] (Springer Nature, 2022)
Zirconia (ZrO2) is a well-known and widely used ceramic in engineering applications and is even termed as ‘ceramic steel’ in its tetragonal stabilised phase (TZP). However, even the tetragonal zirconia has some issues with low fracture toughness and attempts to enhance its toughness have been researched thoroughly. A recent and promising toughening method is the addition of other components to the TZP ceramic matrix. Different additives are used with nanocomponents as a major means of zirconia toughening, using advanced sintering and processing techniques such as flash sintering and spark plasma sintering. This work aims to produce a composite with zirconia matrix adding nanocomponents (carbon nanotubes) to modify and analyse the composite properties, using common methods of processing and sintering. With said common methods (furnace sintering and hydrothermal mixing), we produced ZrO2-CNT composites with 1.0 and 2.0% in weight of CNTs and analysed the nanotubes’ presence and their influence on the composite properties after sintering. The composite showed good results, with CNTs’ integrity achieved in the composites, as observed by scanning electron microscopy. Composite density was as high as 96% with 1.0 wt% of CNTs and, for mechanical properties, hardness suffered a little loss in the composites when compared to the pure zirconia.
Keywords: Carbon nanotubes; Composite; Fractography; Reducing atmosphere; Zirconia